2019
DOI: 10.1016/j.artmed.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Deep convolutional neural networks for brain image analysis on magnetic resonance imaging: a review

Abstract: In recent years, deep convolutional neural networks (CNNs) have shown record-shattering performance in a variety of computer vision problems, such as visual object recognition, detection and segmentation. These methods have also been utilised in medical image analysis domain for lesion segmentation, anatomical segmentation and classification. We present an extensive literature review of CNN techniques applied in brain magnetic resonance imaging (MRI) analysis, focusing on the architectures, pre-processing, dat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
172
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 322 publications
(194 citation statements)
references
References 113 publications
0
172
0
3
Order By: Relevance
“…Machine learning as the science of “artificial intelligence” (i.e., how computers learn from data), is rapidly evolving to include healthcare applications that could revolutionize medical imaging and diagnostics globally. Machine learning models for health are often based on convolutional neural networks (CNNs); the type of deep learning algorithms commonly applied to image classification and segmentation . Applications directly relevant to women's reproductive health include: reproductive medicine; obstetric imaging; breast imaging; and cervical cancer screening …”
Section: Machine Learning In Women's Healthmentioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning as the science of “artificial intelligence” (i.e., how computers learn from data), is rapidly evolving to include healthcare applications that could revolutionize medical imaging and diagnostics globally. Machine learning models for health are often based on convolutional neural networks (CNNs); the type of deep learning algorithms commonly applied to image classification and segmentation . Applications directly relevant to women's reproductive health include: reproductive medicine; obstetric imaging; breast imaging; and cervical cancer screening …”
Section: Machine Learning In Women's Healthmentioning
confidence: 99%
“…Machine learning models for health are often based on convolutional neural networks (CNNs); the type of deep learning algorithms commonly applied to image classification and segmentation. [4][5][6] Applications directly relevant to women's reproductive health include: reproductive medicine 7 ; obstetric imaging 8,9 ; breast imaging 4,10 ; and cervical cancer screening. [11][12][13] In their recent study published in the Journal of the National Cancer Institute, Hu and colleagues assessed the performance of a machine learning model to evaluate cervical images for cancer screening.…”
Section: Machine Learning In Women's Healthmentioning
confidence: 99%
“…Convolutional neural networks are evolving as the state-of-art image segmentation techniques for brain MRI (Bernal et al, 2019). With deep learning network architectures, several automatic features can be observed by the network with no need of prior hand-crafted design .…”
Section: Introductionmentioning
confidence: 99%
“…After a review of these works in the literature, it has been observed that it is still challenging to determine which method performs the best classification to diagnose Alzheimer's disease from MR image data sets. CNNs are powerful for feature detection and extraction for brain image analysis . Therefore, in this work, we have motivated by the recent works and proposed a new fully automated robust 3D CNN architecture.…”
Section: Introductionmentioning
confidence: 99%
“…CNNs are powerful for feature detection and extraction for brain image analysis. 36 Therefore, in this work, we have motivated by the recent works and proposed a new fully automated robust 3D CNN architecture. In this architecture, three full-connected layers for differentiation of subjects and five convolutional layers for feature extraction have been used.…”
Section: Introductionmentioning
confidence: 99%